Raja Ali Haji dan Pemikiran Kebahasaannya: Studi Terhadap Kitāb Bustan Al-khatibin li As-subyān al-Muta’allimin. - M Mustari (Al-Jami'ah: Journal of Islamic Studies, 1998)
At  the  time when the political, military and economic power of the Riau  Empire went  down as a consequence  of the colonialization and division  of Melayu into  two  poles,   Singapore  and Semenanjung Tanah Melayu  (the  North Melayu   was under the colonialization of the British) and  the islands   of Riau (the South Melayu was under the colonialization of the  Dutch),  people were eager to preserve the Melayu and Islamic traditional  values  which  were inherited from their  ancestors. This event, in turn, raised   some defensive fights by means   of the Islamic culture and languages. Kitab Bustan al-Katibin of Raja Ali Hajjis one of the scholarly answers to the need of the Melayu grammar, which, at the sometime, helps to set   the character of Riau as   a center for culture and language training in the 19” century.  As the first book of Melayu grammar, this book, on the one hand, could fill the lacunae of resources on the subject. But on the other hand, the kitab was not successful enough to satisfy the need for a good grammar book which represents the character of the Melayu language, it only absorbed the Arabic grammar. Thus, the significance of the book lies on Raja Ali Haji's thought of Islam, language, and Melayu, and not on the aspect of the grammar. In short, the "kitab" can be seen as the reflection on of the Melayu Riau    intellectuals of the time in guiding their society to completely undestand the Islamic doctrines.